Impact of postoperative cognitive decline in quality of life: a prospective study - Borges,Joana (2017)
Abstract Background Regardless the progress in perioperative care postoperative cognitive decline (PCD) has been accepted unequivocally as a significant and frequent complication of surgery in older patients. The aim of this study was to evaluate the incidence of postoperative cognitive decline and its influence on quality of life three months after surgery. Methods Observational, prospective study in a Post-Anesthesia Care Unit (PACU) in patients aged above 45 years, after elective major surgery. Cognitive function was assessed with Montreal Cognitive Assessment (MOCA); Quality of life (QoL) was assessed using SF-36 Health Survey (SF-36). Assessments were performed preoperatively (T0) and 3 months after surgery (T3). Results Forty-one patients were studied. The incidence of PCD 3 months after surgery was 24%. At T3 MOCA scores were lower in patients with PCD (median 20 vs. 25, p = 0.009). When comparing the median scores for each of SF-36 domains, there were no differences between patients with and without PCD. In patients with PCD, and comparing each of SF-36 domains obtained before and three months after surgery, had similar scores for every of the 8 SF-36 areas while patients without PCD had better scores for six domains. At T3 patients with PCD presented with higher levels of dependency in personal activities of daily living (ADL). Conclusion Three months after surgery patients without PCD had significant improvement in MOCA scores. Patients with PCD obtained no increase in SF-36 scores but patients without PCD improved in almost all SF-36 domains. Patients with PCD presented higher rates of dependency in personal ADL after surgery.